PASS Cambridge BEC Vantage Student's Book: an examination preparation sources Update for the revised exam. - Ian, Wood; Sanderson, Paul; Williams, Anne (Oxford : Summertown Publishing, 2001)
Language and Literature
Keywords: Pass cambridge; BEC; Vantage; English Language; English Skill; Pass Cambridge